Acoustic pattern evaluation during cementless hip arthroplasty surgery may be a new method for predicting complications - Morohashi Itaru; Iwase Hideaki; Kanda Akio; Sato Taichi; Homma Yasuhiro; Mogami Atsuhiko; Obayashi Osamu; Kaneko Kazuo (SICOT-J, 2017)
Background: Although surgeons must perform implantation of the cementless stem during total hip arthroplasty (THA) without complications, assessment is left to the surgeon’s intuitive judgement, which could contain inter/intra-observer bias variety. We therefore asked (1) whether the sound created during the stem implantation could be evaluated objectively and (2) whether those sounds are correlate to the complication specific to the cementless stems. Our hypothesis is that the sounds produced during stem insertion could be quantified and related to the complications.